If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3q+122=9q+9
We move all terms to the left:
3q+122-(9q+9)=0
We get rid of parentheses
3q-9q-9+122=0
We add all the numbers together, and all the variables
-6q+113=0
We move all terms containing q to the left, all other terms to the right
-6q=-113
q=-113/-6
q=18+5/6
| 3(2y-3)=-33 | | 2(3a-2)-(a+3)=8 | | -1+5(4x-4)=9x+12 | | (w+2)^2=2w^2+5w-26 | | x²+3x-143=0 | | 2x+7+x=106 | | P=4x+9x-5 | | 6(2+k)5k=0 | | 4x-7=5+2x | | y=0.5*2 | | 3x+2/3=1/10 | | 3(2y-3=-3 | | 6x^2-2=7 | | -27=1.8n+32 | | -5/9r=10 | | 14/2b^2-8=0 | | 3^z=81^2 | | 8/9*x-17=15 | | 17x=5(3x+2) | | 16^x-2=3^4x | | 80+.30x=60+.8x | | 18/6a=4a(a+3) | | 2x9=1x5 | | 8/9x-17=15 | | 5x+11=4(x+6) | | 4x-7=5=2x | | -4(-2b-7)=41 | | 2x+(-3x)=4(-2) | | 2x25=6x9 | | -5x-25=25 | | -18v+16v=20 | | 89+.30x=60+.8x |